2005
DOI: 10.1002/ajmg.a.30910
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of Xq26.2-q27.1, includingSOX3, in a mother and daughter with short stature and dyslalia

Abstract: Duplications of the distal long arm of the X chromosome are rare and carrier females are usually phenotypically normal. We report on a 14-year-old short statured (height and weight <3rd centile) girl with dup(X)(q26.2q27.1) inherited from a short mother. The proband has minor dysmorphic features, lordosis, lack of menarche, late signs of puberty, low prepuberal levels of gonadotrophins and steroids, but borderline low IGF-1 and normal IGF-Bp3 serum levels. Both the proposita and her mother have severe speech p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Some individuals have been reported to have varying combinations of deficiencies of other hormones including adrenocorticotrophin (ACTH), TSH or gonadotrophins, and complete panhypopituitarism has been documented in some cases. Unaffected carrier females in these pedigrees show preferential inactivation of the duplicated X chromosome; however, a rare family with five affected females presenting with short stature secondary to hypopituitarism, speech and language problems, hearing impairment and facial dysmorphism has also been reported with a 7.5 Mb duplication of chromosome Xq26.2-q27.1 (40). The authors suggested that the duplication may disrupt SOX3 resulting in hemizygosity in affected females, although this was not confirmed at the molecular level.…”
Section: Sox3mentioning
confidence: 99%
“…Some individuals have been reported to have varying combinations of deficiencies of other hormones including adrenocorticotrophin (ACTH), TSH or gonadotrophins, and complete panhypopituitarism has been documented in some cases. Unaffected carrier females in these pedigrees show preferential inactivation of the duplicated X chromosome; however, a rare family with five affected females presenting with short stature secondary to hypopituitarism, speech and language problems, hearing impairment and facial dysmorphism has also been reported with a 7.5 Mb duplication of chromosome Xq26.2-q27.1 (40). The authors suggested that the duplication may disrupt SOX3 resulting in hemizygosity in affected females, although this was not confirmed at the molecular level.…”
Section: Sox3mentioning
confidence: 99%
“…Usually, females with duplications on the X-chromosome are phenotypically normal, as in most cases the duplicated region is subjected to inactivation. However, in females with Xq duplications ID and various other features have been reported (armstrong et al 2003;aughton et al 1993;Garcia-Heras et al 1997;ricks et al 2010;sanlaville et al 2005;stankiewicz et al 2005;tachdjian et al 2004). the prevalence of duplications comprising more proximal regions of Xq is yet unknown and duplications of Xq25 and Xq26 have been reported in only a few cases (armstrong et al 2003;Bauters et al 2005;Garcia-Heras et al 1997;Madrigal et al 2010;ricks et al 2010;schroer et al 2012;stankiewicz et al 2005;tachdjian et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Few cases of dup(Xq) have been described in females, and the abnormal phenotype usually includes short stature, developmental delay, hypogonadism and other dysmorphic anomalies. As a consequence of selection against cells with abnormal X in carrier females, most dup(Xq) are inactivated, and females appear phenotypically normal (Armstrong et al, 2003;Stankiewicz et al, 2005). In our dup(Xq) case, we believe that the clinical data observed in this patient were probably due to the 45,X cell line.…”
Section: Discussionmentioning
confidence: 65%